"Estandarización del proceso de obtención en licorespirituoso con hojas de mandarina (Cirus reticulata) y hierba luisa (Cymbopogon citratus) - Chancay González, Robert Alexander (2019)
Throughout our history the presence of alcoholic beverages has had an impact from the oldest civilizations to the industrialization and generation of liquors with added value. The research will be carried out in the agroindustrial workshops and laboratories of the “La María” campus. The obtaining of the raw material that is the juice of cane to be fermented will be coming from the jurisdiction of the Canton Pangua (The Heart), while the tangerine and lemongrass leaves were obtained in the experimental farm. The study aims to determine the effect of maturity and variations of tangerine leaves mixed with lemongrass on the absorption of the spirit alcoholic beverage, being part of its characters evaluated by a sensory analysis. Its distillation will be carried out using a simple stainless steel column distiller and its absorption analysis was carried out using a spectrophotometer. As the data made were a completely randomized block design (DBCA), the best a2b0 treatment (0.16% of ripe tangerine leaves with Hierbaluisa) was determined highlighting favorable sensory characteristics and an absorbance of 0.91 a 354 nm establishing as a blue hue in the spirits drink. The composition of the liquor showed a concentration of 4.67 mg / 100 cm³ in methanol becoming a minimum irrigation product for the consumer. The results of the research generated positive results, obtaining 3 crystalline treatments and 6 of bluish hue fulfilling the objectives of the same. Key words: Tone, Distillation, Absorbancia, Chromatography, essential